2017
DOI: 10.4236/wjet.2017.53b013
|View full text |Cite
|
Sign up to set email alerts
|

The Irony of Flood Risks in African Dryland Environments: Human Security in North Cameroon

Abstract: North Cameroon, though located in an arid environment, ironically also suffers from the serious threat of flooding in the region. This article examines contemporary challenges resulting from frequent flooding in North Cameroon. Using Cutter's "Hazard of Place Model" of vulnerability as the conceptual basis, the article triangulates data from a variety of sources to analyze environmental risks, social and biophysical vulnerability and flood impact, including flood risk management in North Cameroon. The findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 12 publications
3
31
0
Order By: Relevance
“…Findings are also similar to limited studies covering other parts of the country that showed that destruction of homes, crops, livestock loss from flash floods causes production and income loss (Molua, 2012;Balgah et al, 2015;Bang et al, 2017). This adds credence to the generality of the results.…”
Section: Impact Of Frequent Flooding On Livelihood Assets and Food Sesupporting
confidence: 83%
See 2 more Smart Citations
“…Findings are also similar to limited studies covering other parts of the country that showed that destruction of homes, crops, livestock loss from flash floods causes production and income loss (Molua, 2012;Balgah et al, 2015;Bang et al, 2017). This adds credence to the generality of the results.…”
Section: Impact Of Frequent Flooding On Livelihood Assets and Food Sesupporting
confidence: 83%
“…Northern Cameroon, though located in an arid environment, has been experiencing recurring devastating annual flash floods in the last decade (Bang et al, 2017). The 1999 and 2012 floods compromised the Lagdo and Maga Dams -forcing the release of water from the reservoir and exacerbating the flooding downstream.…”
Section: Food Security In Northern Cameroonmentioning
confidence: 99%
See 1 more Smart Citation
“…There are mainly five types of floods: river flood, flash flood, inland flood, storm surge, coastal flood [8,9]. Floods are considered as one of the most frequent global hazards [10]. Floods account for approximately 40% of natural disasters and will possibly become more recurrent and severe due to global warming [11].…”
Section: Introductionmentioning
confidence: 99%
“…Cameroon's geo-physical location, tectonic history and climate makes her one of the most susceptible countries affected by natural hazards in Africa. The regularity and devastation caused by such hazards along the active Cameroon Volcanic Line (CVL) are becoming more frequent and even more disastrous, affecting livelihood assets including human, social, financial, natural, physical capital [10,16]. The country is becoming more prone to and persistently hit by floods and droughts but also by mud flows, rock fall, lahars, volcanic eruptions, toxic gas emissions, earth tremors and landslides which occur on a regular annual pattern.…”
Section: Introductionmentioning
confidence: 99%